2016
DOI: 10.1007/s11069-016-2505-8
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of observed and predicted ground motions from the 2015 MW7.8 Gorkha, Nepal, earthquake

Abstract: We use 21 strong motion recordings from Nepal and India for the 25 April 2015 moment magnitude (M W ) 7.8 Gorkha, Nepal, earthquake together with the extensive macroseismic intensity data set presented by Martin et al. (Seism Res Lett 87:957-962, 2015) to analyse the distribution of ground motions at near-field and regional distances. We show that the data are consistent with the instrumental peak ground acceleration (PGA) versus macroseismic intensity relationship developed by Worden et al. (Bull Seism Soc … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
15
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 52 publications
7
15
1
Order By: Relevance
“…Hence, the U.S. Geological Survey ShakeMap largely relied on empirical equations for estimating ground motion parameters. However, the estimated PGA values appeared to be consistent with field observations (Collins & Jibson, ) and macroseismic intensities, particularly within 200 km of the fault (Hough et al, ); all HPPs in our database are also within this distance.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Hence, the U.S. Geological Survey ShakeMap largely relied on empirical equations for estimating ground motion parameters. However, the estimated PGA values appeared to be consistent with field observations (Collins & Jibson, ) and macroseismic intensities, particularly within 200 km of the fault (Hough et al, ); all HPPs in our database are also within this distance.…”
Section: Discussionsupporting
confidence: 88%
“…Measures of ground motion during the Gorkha earthquake are not well constrained due to limited ground motion observations for near‐field distances. The main shock was recorded by six near‐field instruments in the Kathmandu Valley (Hough et al, ). Hence, the U.S. Geological Survey ShakeMap largely relied on empirical equations for estimating ground motion parameters.…”
Section: Discussionmentioning
confidence: 99%
“…The spatial distribution of EMS intensities in the Kathmandu Valley is qualitatively similar to that observed in earlier studies, with the lowest values in the central, deepest part of the valley (Figure 3), and somewhat higher values around the periphery of the valley and in the adjacent foothills. Figure 3 The spatial distribution of intensities throughout the near-field region reveals some differences with respect to the results of earlier studies (Hough et al 2016. Consistent with the earlier studies, we find intensities to be generally higher toward the northern edge of the rupture, but unlike the earlier studies the swath of high intensities is less narrowly concentrated along the northern edge; instead, there is a swath of relatively high intensities close to the along-strike midline of the rupture.…”
Section: Synthesis and Analysis Of Datasupporting
confidence: 76%
“…The impact of having different questions in a questionnaire on the intensity scale is unknown and will be investigated in this study. Hough et al (2016) reported substantial differences between the macroseismic datasets of the Nepal Ghorka earthquake.…”
Section: Comparing Institutional Questionnairesmentioning
confidence: 99%